Front Cover: The Influence of the Amino Acid Side Chains on the Raman Optical Activity Spectra of Proteins (ChemPhysChem 1/2019). Issue 1 (2nd January 2019) - Mensch, Carl; Johannessen, Christian
Abstract : The Front Cover shows the spectroscopic response to the conformational flexibility of protein side‐chains as probed by Raman optical activity. More information can be found in the Article by C. Mensch and C. Johannessen onpage 42 in Issue 1, 2019 (DOI:10.1002/cphc.201800924 ).